2017
DOI: 10.1007/s13204-017-0585-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growth parameters on In-droplet-assisted growth of InAs nanowires on silicon

Abstract: The influence of growth parameters on the morphology and density of InAs nanowires (NWs) grown on bare Si substrates using Indium (In) droplets as catalyst is investigated. By tuning the growth temperature, V/III flux ratio, and growth rate, the diameter and yield of asgrown NWs were controllably manipulated. It is demonstrated that the In-droplet-assisted growth of InAs NWs can only be realized on bare Si within a relatively narrow growth window of 420-475°C. Below 420°C, NWs' growth is kinetically limited, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The axial growth rate of 4.4 nm s À1 obtained here is even higher than the maximum growth rate of Au-catalyzed InAs NWs grown by metal-organic vapor phase epitaxy at 450 C (3.1 nm s À1 ), [15] while the MBE growth rate at 450 C is below 1 nm s À1 . [16] This result is even more surprising if we consider that most In atoms remain in the parasitic islands between the NWs, clearly seen in Figure 1b. We attribute the large L h i=H ratio of our NWs to: 1) low temperature, which suppresses desorption of In from the substrate surface, NW sidewalls, or catalyst nanoparticles, and 2) narrow NW diameter.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The axial growth rate of 4.4 nm s À1 obtained here is even higher than the maximum growth rate of Au-catalyzed InAs NWs grown by metal-organic vapor phase epitaxy at 450 C (3.1 nm s À1 ), [15] while the MBE growth rate at 450 C is below 1 nm s À1 . [16] This result is even more surprising if we consider that most In atoms remain in the parasitic islands between the NWs, clearly seen in Figure 1b. We attribute the large L h i=H ratio of our NWs to: 1) low temperature, which suppresses desorption of In from the substrate surface, NW sidewalls, or catalyst nanoparticles, and 2) narrow NW diameter.…”
Section: Resultsmentioning
confidence: 90%
“…The axial growth rate of 4.4 nm s −1 obtained here is even higher than the maximum growth rate of Au‐catalyzed InAs NWs grown by metal–organic vapor phase epitaxy at 450 °C (3.1 nm s −1 ), [ 15 ] while the MBE growth rate at 450 °C is below 1 nm s −1 . [ 16 ]…”
Section: Resultsmentioning
confidence: 99%
“…As the growth temperature is increased, the NP become smaller and so both axial and radial growth rate decrease. Moreover, at high growth temperature In desorption starts to be sizable [ 60 ] so that both growth rates decrease. Moreover, considering the As-line pressure series, we found that when the growth conditions preserve an In droplet with β > 90° on top of the NWs, both axial and radial growths are enhanced by increasing F As , meaning that both VLS and VS growth are As-limited.…”
Section: Resultsmentioning
confidence: 99%
“…In self-catalyzed MBE, the indium catalyst is obtained either by in-situ deposition prior to growth [144] or by initiating growth under indium rich conditions [145]. The NW morphology is very sensitive to the growth parameters such as the temperature and the vapor phase composition.…”
Section: Iv3 Growth Of Inas Nws On Simentioning
confidence: 99%
“…In MBE and CBE, several groups showed that VS growth of InAs NWs was mainly limited by the surface diffusion of adatoms, which does not favor a pure crystalline quality of NWs that exhibit a high density of twin planes, stacking faults and alternating ZB/WZ segments along the growth axis [143,144,151]. MOVPE provided also very promising results in the case of SAG, even though the wires did not exhibit a pure crystalline quality all along the NWs length limited to few microns [152,153].…”
Section: Growth Of Inas Nws On Simentioning
confidence: 99%